Boundary integrationism and its subject: shifts and continuities in the EU framework on migrant integration - Dodevska, Iva (Journal of ethnic and migration studies, 2024)
The European Union emerged as an important actor in debates on 'migrant integration', yet remains understudied. This paper critically maps the EU Framework on migrant integration, outlining the ruptures and continuities that have shaped EU's approach to 'diversity governance' in the past three decades. I propose a typology of the (sometimes opposing) discourses that converge in the EU migrant integration policy, differentiating between neoliberal, egalitarian (welfarist), securitarian and boundary integrationism. I argue that while the early predominantly welfarist and neoliberal discourse on integration was only vaguely interested in questions of values and identity, the recent reformulation of the EU's integrationist strategy represents a break from universalist ideas of a 'European community'. In particular, the Commission under von der Leyen adopted a more nativist and securitarian discourse that frames 'integration' as a wager in an alleged civilizationist clash between the liberal and the 'illiberal' world. I argue that the rising importance of adherence to liberal values as a proxy for 'integration', the reinvention of 'European values' as cultural values springing from the Judeo-Christian liberal tradition, and drawing new boundaries around the subject of integration are three developments that amount to an important shift in the European Union's migration and integration agenda.